Anxiety, depression: comorbidity of chronic orofacial pain disorder in temporomandibular joint dysfunction syndrom - Yulia V. Kotsiubinskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Persistent orofacial pain belongs to a group of pain conditions of non-dental etiology affecting the face and mouth, significantly impacting quality of life and having a biopsychosocial nature. Temporomandibular joint pain dysfunction syndrome (TMD) is one of the most common causes of chronic orofacial pain, involving the masticatory muscles. It is a musculoskeletal disorder characterized by pain and discomfort in the muscles and joints responsible for chewing and jaw movement. Psychopathological factors such as anxiety and depression play an important role in the development and maintenance of persistent pain and muscle dysfunction in the orofacial region. Objective: To study the severity of anxiety and depression in patients with chronic orofacial pain associated with temporomandibular joint dysfunction syndrome. Materials: A total of 354 patients with chronic orofacial pain were examined. The clinical picture of their condition was dominated by pain symptoms and pronounced myotonic disorders of the masticatory muscles, which were comorbidly associated with anxiety and depressive disorders (ICD-10 codes: K07.8+F43; F45.8). The average age of the patients was 48.6±12.9 years. Results: The studied group showed significantly higher levels of anxiety and depression compared to the healthy population. These manifestations were mostly subclinical in nature and often presented as somatized complaints, mild anxiety, and self-critical attitudes towards appearance. Patients with complaints of myotonic disorders and orofacial pain without marked symptoms of anxiety and depression constituted 52.0% of the group. Among the patients, 6.8% had pronounced anxiety disorders on the background of orofacial dysfunction, while 41.2% were diagnosed with depressive disorders of varying severity. Both somatic and psychological factors are involved in the development of TMD pain dysfunction and comorbid anxiety-depressive disorders, making it reasonable to approach this pathology from a psychosomatic perspective.